ANALYSIS OF RISK MANAGEMENT DEVELOPMENT AS A STRATEGIC EFFORT FOR CRIME PREVENTION IN PURI BOJONG LESTARI 2 HOUSING COMPLEX, BOGOR - Muhammad Rafi Abidazmi; Monica Margaret (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Rapid urbanization in the Jabodetabek region has triggered significant security challenges, particularly concerning the increasing incidence of property-related crimes. One affected area is Bojong Gede District, Bogor Regency, which has experienced rapid residential development. This study focuses on Puri Bojong Lestari 2 Housing Complex, which, despite its physical and demographic growth, continues to face serious challenges in environmental security due to its open layout, weak security systems, and numerous unmonitored access roads. This research adopts a descriptive qualitative approach to analyze the development of risk management as a crime prevention strategy, grounded in the theory of Situational Crime Prevention (SCP). Data findings indicate persistent weaknesses in the implementation of security systems, including inadequate surveillance, insufficient physical security infrastructure, and low levels of community social participation. The integration of risk management with Situational Crime Prevention (SCP) is believed to enable the development of a more adaptive and effective crime prevention system, encompassing the five key techniques outlined in SCP theory. This study provides practical recommendations for housing managers and policymakers to establish a systematic community security framework.